The "Hard" SDR : An Exploratory Analysis - Thakur, Subhash (IMF Working Papers; Working Paper ;, 1994)
There has been considerable interest in recent years in the possibility of hardening the SDR, motivated by the desire for an international yardstick of monetary stability. This paper explores various ideas aimed at hardening the SDR in the light of the previous debate on the valuation of the SDR. The paper shows that the construction and implementation of a 'hard' SDR which would preserve its purchasing power over goods and services is technically feasible and illustrates this by monthly computations covering the period from July 1974 to July 1993.